Kajian arca Agastya bertubuh ramping koleksi Museum Mpu Purwa Kota Malang - Rakai Hino Galeswangi (Berkala Arkeologi, 2021)
This study aims to examine and identify the place of origin of the slender Agastya statue (arca) stored in the Mpu Purwa Museum, Malang. The object of study is the Agastya depicted with a slender stomach, partially curled and partially loose on the back hair-style, and holding the trident weapon from its backrest. The research method is qualitative descriptive, using inductive reasoning with the sense of analytical description. This research uses analysis of iconography, ecology, contextual, and historical approach. The result shows that the slender Agastya is locally made with high quality and influenced by the Gupta-Indian style, which appeared in the VIII to IX centuries in Central Java.  The origin of Agastya statue also known as part of the Karangbesuki temple ruins in Desa Karangbesuki. The Agastya acts as a Hindu temple mandala statue placed in a niche of the south side wall. These result is expected to be useful for further researches.